Microtubule-dependent modulation of adhesion complex composition. - Daniel H J Ng; Jonathan D Humphries; Adam Byron; Angélique Millon-Frémillon; Martin J Humphries (PLoS ONE)
The microtubule network regulates the turnover of integrin-containing adhesion complexes to stimulate cell migration. Disruption of the microtubule network results in an enlargement of adhesion complex size due to increased RhoA-stimulated actomyosin contractility, and inhibition of adhesion complex turnover; however, the microtubule-dependent changes in adhesion complex composition have not been studied in a global, unbiased manner. Here we used label-free quantitative mass spectrometry-based proteomics to determine adhesion complex changes that occur upon microtubule disruption with nocodazole. Nocodazole-treated cells displayed an increased abundance of the majority of known adhesion complex components, but no change in the levels of the fibronectin-binding α5β1 integrin. Immunofluorescence analyses confirmed these findings, but revealed a change in localisation of adhesion complex components. Specifically, in untreated cells, α5-integrin co-localised with vinculin at peripherally located focal adhesions and with tensin at centrally located fibrillar adhesions. In nocodazole-treated cells, however, α5-integrin was found in both peripherally located and centrally located adhesion complexes that contained both vinculin and tensin, suggesting a switch in the maturation state of adhesion complexes to favour focal adhesions. Moreover, the switch to focal adhesions was confirmed to be force-dependent as inhibition of cell contractility with the Rho-associated protein kinase inhibitor, Y-27632, prevented the nocodazole-induced conversion. These results highlight a complex interplay between the microtubule cytoskeleton, adhesion complex maturation state and intracellular contractile force, and provide a resource for future adhesion signaling studies. The proteomics data have been deposited in the ProteomeXchange with identifier PXD001183.